TARGETING POULTRY PATHOGENS: INSIGHTS FROM ISOLATION, ANTIBIOGRAM ANALYSIS, AND ESSENTIAL OIL MODULATION OF KLEBSIELLA SPECIES - Ambreen Rafique; Nida Baig; Iqra Rafiq; Aneela Mehboob; Asma Naim (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Poultry meat, a staple in global diets, is known to act as a reservoir for contamination of bacteria. The presence of MDR strains in poultry products has raised concerns about the transmission of genes coding for either virulence or resistance, necessitating thorough investigations into alternative antimicrobial agents for effective bacterial control. This study aimed to investigate the antibacterial activity of commercial essential oils against Klebsiella isolates obtained from poultry meat, as well as to evaluate potential additive effects when combined with antibiotics. Briefly, 150 chicken meat samples (raw) were collected and characterized by conventional methods. Antibiogram analysis and antimicrobial activity of essential oils of the identified Klebsiella isolates was determined by Kirby Bayer disc diffusion and agar well diffusion assay respectively. The antibiotic susceptibility testing revealed varying degrees of resistance among the Klebsiella isolates, highlighting the importance of alternative antimicrobial agents. Clove and cinnamon essential oils exhibited potent antibacterial activity against 100% of the isolates with zone of inhibition (ZOI) ranges from 20-32 and 15-21.6mm. Compared to this, rosemary and peppermint were less effective against the isolated strains given the activity only against 14.2% and 28.5% isolates. Further investigation into the potential additive effects of clove and cinnamon oils in combination with antibiotics revealed promising results. However, an antagonistic interaction was observed when clove oil was combined with gentamicin, suggesting caution in the concurrent use of certain essential oils and antibiotics. In conclusion, clove and cinnamon essential oils represent promising natural antimicrobial agents with clove oil demonstrating superior efficacy against Klebsiella isolated from poultry meat. The additive effects observed underscore the potential for synergistic antimicrobial strategies combining essential oils with conventional antibiotics. However, careful consideration of potential interactions, such as antagonism, is necessary to ensure the effectiveness of combined therapies and mitigate the emergence of antimicrobial resistance.